Formation of ferromagnetic molecular thin films from blends by annealing - Robaschik, Peter; Ma, Ye; Din, Salahud; Heutz, Sandrine (Beilstein Journal of Nanotechnology, 2017)
We report on a new approach for the fabrication of ferromagnetic molecular thin films. Co-evaporated films of manganese phthalocyanine (MnPc) and tetracyanoquinodimethane (TCNQ) have been produced by organic molecular beam deposition (OMBD) on rigid (glass, silicon) and flexible (Kapton) substrates kept at room temperature. The MnPc:TCNQ films are found to be entirely amorphous due to the size mismatch of the molecules. However, by annealing while covering the samples highly crystalline MnPc films in the β-polymorph can be obtained at 60 °C lower than when starting with pure MnPc films. The resulting films exhibit substantial coercivity (13 mT) at 2 K and a Curie temperature of 11.5 K.
Keywords: co-deposition; molecular spintronics; organic thin films; phthalocyanines; tetracyanoquinodimethane (TCNQ)